SOCIAL INCLUSION OF STUDENTS WITH AUTISM SPECTRUM DISORDER IN INDONESIAN MAINSTREAM CLASSROOMS: A SOCIAL-PSYCHOLOGICAL STUDY - Luluk Alfiya; Nina Anis; Nurul Huda (Yayasan Adra Karima Hubbi, 2025)
Students with Autism Spectrum Disorder (ASD) often face significant challenges in achieving full social inclusion within mainstream educational settings, particularly in countries with limited inclusive education infrastructures such as Indonesia. Despite the existence of inclusive education policies, actual practices in schools frequently fall short of supporting the social integration of students with ASD. This study aims to examine the extent and nature of social inclusion experienced by students with ASD in Indonesian mainstream classrooms from a social-psychological perspective. A mixed-methods design was employed, incorporating classroom observations, structured interviews with teachers, parents, and students, and quantitative surveys measuring peer acceptance and emotional well-being. The findings indicate that while policy frameworks endorse inclusion, students with ASD often experience social isolation, limited peer interaction, and inadequate teacher preparedness. Social acceptance was highly dependent on the teacher's attitude, peer training, and availability of support systems. The study concludes that achieving meaningful inclusion requires more than policy—it demands deliberate social and psychological interventions at the classroom level. These findings call for teacher training, inclusive pedagogy, and school-wide empathy-building programs to promote equitable learning environments for all students.